2009
DOI: 10.1111/j.1460-9568.2009.06962.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenetics of food anticipation

Abstract: Circadian clocks enable the organisms to anticipate predictable cycling events in the environment. The mechanisms of the main circadian clock, localized in the suprachiasmatic nuclei of the hypothalamus, involve intracellular autoregulatory transcriptional loops of specific genes, called clock genes. In the suprachiasmatic clock, circadian oscillations of clock genes are primarily reset by light, thus allowing the organisms to be in phase with the light-dark cycle. Another circadian timing system is dedicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 142 publications
(182 reference statements)
1
48
0
Order By: Relevance
“…Rats that received 50% restriction as two meals/day had significantly more adipose tissue mass than the other restricted groups. One reason why this effect may happen is that when CR animals are fed a single meal they show a large amount of anticipatory activity in the period prior to the meal arriving (Challet et al, 2009;Mistlberger, 1994) and they subsequently eat the meal rapidly. It has been shown that there is a correlation between anticipatory activity and how fast the food is eaten, suggesting both are perhaps driven by the experience of hunger.…”
Section: Variation In the Experimental Protocols For Caloric Restrictmentioning
confidence: 96%
“…Rats that received 50% restriction as two meals/day had significantly more adipose tissue mass than the other restricted groups. One reason why this effect may happen is that when CR animals are fed a single meal they show a large amount of anticipatory activity in the period prior to the meal arriving (Challet et al, 2009;Mistlberger, 1994) and they subsequently eat the meal rapidly. It has been shown that there is a correlation between anticipatory activity and how fast the food is eaten, suggesting both are perhaps driven by the experience of hunger.…”
Section: Variation In the Experimental Protocols For Caloric Restrictmentioning
confidence: 96%
“…However, the anatomical substrate(s) and molecular machinery of the so-called "food-entrainable oscillator (FEO)" remains to be unknown. Moreover, despite the well characterized circadian nature of FAA, the involvement of canonical clock genes remains controversial (Challet et al, 2009). For example, one study demonstrated that arrhythmic Bmal1 Ϫ/ Ϫ mice also lack food-entrainable circadian rhythms (Fuller et al, 2008), while another two studies reported normal FAA of the same mouse line (Pendergast et al, 2009;Storch and Weitz, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Mammals (rodents) possess an endogenous circadian clock known as light-entrainable oscillator (LEO) which is synchronised by photoperiodic signals. It is thought that rodents' LEO is localised in the suprachiasmatic nucleus (SCN) of the hypothalamus (Stephan and Zucker, 1972;Moore and Eichler, 1977;Landry et al, 2007;Caba et al, 2008;Challet et al, 2009), synchronising light-related rhythms. In fish, little is known on this topic (Sanchez-Vazquez et al, 1995b), but in most fishes a circadian rhythm of locomotor activity has been proposed which appears to be feeding-entrained (Kavaliers, 1979(Kavaliers, , 1980Tabata et al, 1989;Azzaydi et al, 2007).…”
Section: Introductionmentioning
confidence: 99%